"We Need to Learn from What we Have Learned!": The Possible Impact of Covid-19 on the Education and Training of Chaplains. (April 2021) - Flynn, Eleanor; Tan, Heather; Vandenhoeck, Anne
The responses of chaplains providing care in health services during the Covid-19 pandemic showed that they both learned new skills and taught these to others while working in environments made unfamiliar by personal protective equipment and social distancing. This paper discusses the responses of the participants as they relate to education and training as well as suggesting new content and styles of education to meet the needs of chaplains in future similar events.